Analyses of antioxidant status and nucleotide alterations in genes encoding antioxidant enzymes in patients with benign and malignant thyroid disorders - Ramli, Nur Siti Fatimah; Junit, Sarni Mat; Ng, Khoon Leong; Razali, Nurhanani; Jayapalan, Jaime Jacqueline; Aziz, Azlina Abdul (PeerJ, 2017)
Background: Synthesis of thyroid hormones and regulation of their metabolism involve free radicals that may affect redox balance in the body. Thyroid disorders causing variations in the levels of thyroid hormones may alter cellular oxidative stress. The aim of this study was to measure the antioxidant activities and biomarkers of oxidative stress in serum and red blood cells (RBC) of patients with benign and malignant thyroid disorders and to investigate if changes in the antioxidant activities in these patients were linked to alterations in genes encoding the antioxidant enzymes. Methods: Forty-one patients with thyroid disorders from University of Malaya Medical Centre were recruited. They were categorised into four groups: multinodular goitre (MNG) (n = 18), follicular thyroid adenoma (FTA) (n = 7), papillary thyroid cancer (PTC) (n = 10), and follicular thyroid cancer (FTC) (n = 6). Serum and RBC of patients were analysed for antioxidant activities, antioxidant enzymes, and biomarkers of oxidative stress. Alterations in genes encoding the antioxidant enzymes were analysed using whole exome sequencing and PCR-DNA sequencing. Results: Patients with thyroid disorders had significantly higher serum superoxide dismutase (SOD) and catalase (CAT) activities compared to control, but had lower activities in RBC. There were no significant changes in serum glutathione peroxidase (GPx) activity. Meanwhile, GPx activity in RBC was reduced in PTC and FTC, compared to control and the respective benign groups. Antioxidant activities in serum were decreased in the thyroid disorder groups when compared to the control group. The levels of malondialdehyde (MDA) were elevated in the serum of FTA group when compared to controls, while in the RBC, only the MNG and PTC groups showed higher MDA equivalents than control. Serum reactive oxygen species (ROS) levels in PTC group of both serum and RBC were significantly higher than control group. Whole exome sequencing has resulted in identification of 49 single nucleotide polymorphisms (SNPs) in MNG and PTC patients and their genotypic and allelic frequencies were calculated. Analyses of the relationship between serum enzyme activities and the total SNPs identified in both groups revealed no correlation. Discussion: Different forms of thyroid disorders influence the levels of antioxidant status in the serum and RBC of these patients, implying varying capability of preventing oxidative stress. A more comprehensive study with a larger target population should be done in order to further evaluate the relationships between antioxidant enzymes gene polymorphisms and thyroid disorders, as well as strengthening the minor evidences provided in literatures.